Nutrient availability and nutrient use efficiency in plants growing in the transition zone between land and water. (23rd October 2015) - Cavalli, G.; Baattrup‐Pedersen, A.; Riis, T.
Abstract: The transition zone between terrestrial and freshwater habitats is highly dynamic, with large variability in environmental characteristics. Here, we investigate how these characteristics influence the nutritional status and performance of plant life forms inhabiting this zone. Specifically, we hypothesised that: (i) tissue nutrient content differs among submerged, amphibious and terrestrial species, with higher content in submerged species; and (ii) PNUE gradually increases from submerged over amphibious to terrestrial species, reflecting differences in the availability of N and P relative to inorganic C across the land–water ecotone. We found that tissue nutrient content was generally higher in submerged species and C:N and C:P ratios indicated that content was limiting for growth for ca. 20% of plant individuals, particularly those belonging to amphibious and terrestrial species groups. As predicted, the PNUE increased from submerged over amphibious to terrestrial species. We suggest that this pattern reflects that amphibious and terrestrial species allocate proportionally more nutrients into processes of importance for photosynthesis at saturating CO2 availability, i.e . enzymes involved in substrate regeneration, compared to submerged species that are acclimated to lower availability of CO2 in the aquatic environment. Our results indicate that enhanced nutrient loading may affect relative abundance of the three species groups in the land–water ecotone of stream ecosystems. Thus, species of amphibious and terrestrial species groups are likely to benefit more from enhanced nutrient availability in terms of faster growth compared to aquatic species, and that this can be detrimental to aquatic species growing in the land–water ecotone, e.g. Ranunculus and Callitriche .